1991
DOI: 10.1109/55.82056
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency time-dependent breakdown of SiO/sub 2/

Abstract: Time-dependent dielectric breakdown (TDDB) of thin oxides (8.6-11 nm) is compared under dc, pulse, and bipolar pulse conditions for frequencies up to 4 MHz. Lifetime under unipolar pulse conditions does not deviate largely from that under dc conditions; however, lifetime under bipolar stress conditions increases by a factor of 40 to 100 at frequencies above 10 kHz. The field acceleration of breakdown time is similar for dc and pulse stressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Once the stress is switched to an AC pulse, T BD decreases dramatically, see Fig 3 . For most reliability phenomena (e.g., TDDB, BTI, SILC), typically the AC lifetime is either larger (with recovery) or equal (when recovery is absent) to the derated DC lifetime of the capacitor [14][15][16]. In ferroelectrics, however, the AC TDDB lifetime is orders of magnitude smaller than that at DC bias (Fig.…”
Section: The Puzzle Of Ac Lifetime and Hot Atom Damagementioning
confidence: 99%
“…Once the stress is switched to an AC pulse, T BD decreases dramatically, see Fig 3 . For most reliability phenomena (e.g., TDDB, BTI, SILC), typically the AC lifetime is either larger (with recovery) or equal (when recovery is absent) to the derated DC lifetime of the capacitor [14][15][16]. In ferroelectrics, however, the AC TDDB lifetime is orders of magnitude smaller than that at DC bias (Fig.…”
Section: The Puzzle Of Ac Lifetime and Hot Atom Damagementioning
confidence: 99%
“…In the short pulsewidth regime (less than 100 ns), there is a significant increase in , while for pulses of 100 ns and longer, remains essentially unchanged. The increase of for short pulses has already been observed in thicker SiO barriers, where it was attributed to a combination of charge trap creation and trapped charge relaxation [9]. However, the observed increase of by three orders of magnitude in the MgO tunnel junction data is much larger than what could be expected according to [5].…”
Section: Resultsmentioning
confidence: 63%
“…Previously, other studies have reported on the effects of highfrequency dynamic stress on conventional [2] and reoxidized nitrided oxides [3]. In this letter, we report the first investigation of device performance under high-field dynamic stressing for n-MOSFET's with N,O-annealed gate oxides (oxynitrides).…”
Section: Introductionmentioning
confidence: 91%